2018
DOI: 10.19044/esj.2018.v14n23p117
|View full text |Cite
|
Sign up to set email alerts
|

Residential Customers Satisfaction with Public Water Provision in Ojota, Nigeria

Abstract: Customer satisfaction is a good measure of the quality of service rendered by an enterprise. Hence, this study analyzed the perception of residential customers’ satisfaction with public water provision in Ojota. The analyses was based on customers’ perception of ten selected satisfaction drivers, which were obtained by the administration of a set of structured questionnaire, administered to 400 households, using the systematic sampling technique. The data was analyzed using percentages and a customer satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Customers' willingness to pay water rates was determined based on their overall perception of satisfaction with the services offered. The result of Figure 5 revealed that (19.37%), (31.05%) and (33.90%) respondents were not willing, poorly willing and fairly willing, respectively; while only (10.83%) and (4.84%) respondents were willing and very willing to pay respectively and this finding is similar with [14]. The result from the interview also indicates that customers were willing to pay more if there is a significant improvement in its overall customer services, particularly on the three least rated satisfaction drivers continuous water supply, water pressure and scheduling of water service.…”
Section: Customers' Willingness To Paysupporting
confidence: 76%
See 1 more Smart Citation
“…Customers' willingness to pay water rates was determined based on their overall perception of satisfaction with the services offered. The result of Figure 5 revealed that (19.37%), (31.05%) and (33.90%) respondents were not willing, poorly willing and fairly willing, respectively; while only (10.83%) and (4.84%) respondents were willing and very willing to pay respectively and this finding is similar with [14]. The result from the interview also indicates that customers were willing to pay more if there is a significant improvement in its overall customer services, particularly on the three least rated satisfaction drivers continuous water supply, water pressure and scheduling of water service.…”
Section: Customers' Willingness To Paysupporting
confidence: 76%
“…Customer satisfaction measurement enables an organization to undertake proper evaluation and identify the key drivers that enhance its customer satisfaction [14] and it is defined as the fulfillment and gratification of the need for a stated good or service [12]. The study of customer satisfaction has prime importance to encourage the performance of organizations that provide essential services such as water supply.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential for any water entities, whether public, private or community-managed, to understand that the public's general perception of water is that it is a social good [8]. Customer satisfaction plays a significant role in maintaining balance between customers' demand and utility performance [9,10]. Furthermore, it is necessary to understand how well a utility is performing to identify and prioritize the areas for improvement [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This situation has even worsened as there have not been any appreciable expansion of services since 2008 in spite of the rapid rate of population growth and urban expansion of Lagos. Also, a study by Ohwo and Agusomu (2018) on residential customers satisfaction with public water provision in Ojota (a settlement in Lagos) shows that public water provision in Ojota was perceived as fairly satisfactory, and only 12.21% of the customers were willing to pay for water, based on their overall rating of the services provided by the LWC. This unwillingness to pay for water could lead to poor cost recovery and further increase the woes of the corporation.…”
mentioning
confidence: 99%
“…The Lagos Water Corporation (LWC) supply less than 40% of the households' in the state with potable water. Those that are being supplied are fairly satisfied with the Corporation's services, due to poor customer relations, quality and quantity of water supplied, intermittent supply and many days of no supply (Ohwo & Agusomu, 2018). The inability of the LWC to meet the water needs of the citizens has prompted the State Government to propose the privatization of the Corporation, with the belief that it will enhance its operations, increase funding and meet the water needs of the people.…”
mentioning
confidence: 99%